Late effects of a brief psychological intervention in patients with intermittent claudication in a randomized clinical trial. Issue 6 (6th March 2013) - Cunningham, M. A.; Swanson, V.; Holdsworth, R. J.; O'Carroll, R. E.
<x xml:space="preserve">Abstract</x> Background The authors previously reported the early results of a trial of a brief psychological intervention to increase physical activity in patients with intermittent claudication. After 4 months, participants in the intervention group walked a mean of 1576 more steps per day than control group participants. The present study followed the original participants to determine whether this behaviour change was maintained over 2 years. Methods This was a randomized single‐centre parallel‐group trial. Fifty‐eight patients newly diagnosed with intermittent claudication were assigned randomly to one of two groups. The control group (30 patients) received usual care: lifestyle advice and consultation with a vascular surgeon to agree a treatment plan. The treatment group (28) received usual care plus a brief psychological intervention designed to modify illness and walking beliefs, and develop a personalized walking action plan. The primary outcome was daily steps measured by pedometer. Secondary outcomes included revascularization rate, quality of life and perceived pain‐free walking distance. Follow‐up was conducted at 1 and 2 years. Between‐group differences were analysed by analysis of co‐variance. Results Participants in the brief psychological intervention group walked significantly more than those in the control group. The mean difference at 1 year was 1374 (95 per cent confidence interval 528 to 2220) steps per day and the difference at 2 years was 1630 (495 to 2765) steps per day. Conclusion Modifying illness and walking beliefs, and assisting patients to develop a personalized walking action plan led to increases in walking behaviour in patients with claudication that were maintained for 2 years. Registration number: ISRCTN28051878 (http://www.controlled-trials.com).